2014
DOI: 10.1002/elan.201300631
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electrochemical Oxidation of Flavonols and Calculated Proton Affinity and Electron Transfer Enthalpy in Water

Abstract: Flavonols, a class of flavonoids, are present in flowers, fruits and vegetables. They are jointly responsible for antioxidant activity as free radical acceptors. The redox behaviour of myricetin, quercetin, isorhamnetin, fisetin, morin and kaempferol is investigated using cyclic and differential pulse voltammetry. Quantum chemical calculations of proton affinities and electron transfer enthalpies were performed to identify possible reactive sites and radical species to compare them with measured oxidation pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Actually, the electrochemistry of the different phenolics under study, especially the flavonoids, has been widely studied in conventional media, ,, mainly in aqueous buffered solutions. , The electrochemical behavior of flavonoids is related to the electroactivity of the A and B phenol units, while ring C generally has much less influence (see Figure ). In aqueous media, the redox behavior of these units is characterized by proton–electron transfer mechanisms, which depend on the pH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, the electrochemistry of the different phenolics under study, especially the flavonoids, has been widely studied in conventional media, ,, mainly in aqueous buffered solutions. , The electrochemical behavior of flavonoids is related to the electroactivity of the A and B phenol units, while ring C generally has much less influence (see Figure ). In aqueous media, the redox behavior of these units is characterized by proton–electron transfer mechanisms, which depend on the pH.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, electrochemical techniques have been also proven to be very efficient for evaluating and classifying the antioxidant capacity (antioxidant power) of phenolic compounds on the basis of the measurement of their redox potentials. , It has been demonstrated that the lowest oxidation potential rules the antioxidant power. , In other words, the ring leading to the radical with the lower redox potential corresponds to the active antioxidant moiety in any flavonoid. Indeed, the conjugation between the rings, especially B and A, in the flavonoid radicals is very inefficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myricetin.I nasmuch as myricetin also possesses ac atechol unit (actually,apyrogallol unit) at ring Bs imilar to quercetin, it exhibits high electroactiveb ehaviour.I ts oxidation potential is lower than that of quercetin (Supplementary Fig. S6, [14]), and myricetin yielded two major and three minoro xidation products at m/z 347 and 379 and at m/z 315, 377,4 09 and 441, respectively,a th igher appliedp otentials and at af low rate of 10 mL/min (Fig.4D). Myricetin also forms aq uinone in the first twoelectron, two-proton oxidation step due to the 4'-a nd 3'-OH groups.…”
Section: Ec/esi-ms Of Flavonolsmentioning
confidence: 92%
“…These substances can be studied by electrochemical methodsa st hey easily undergo oxidation, expressed by their low oxidation potentials.I narecent publication, we compared different flavonols usingc yclic and differential pulse voltammetry.B ased on theoretical and mechanistic considerations,a sw ell as structural properties,w er anked these compounds according to their ease of oxidation [14].EC/ESI-MS offers auniquet ool to verify the species postulated in the previous study. In the EC,t he substances can be nearly completely converted usingalarge working electrode surface area and low flow rates to achieve ah igh conversion efficiency.H owever, theoxidised species should be rapidly transported to the mass spectrometert od etect the short-lived intermediates that are generated, thus minimising the number of signals in the mass spectrum.…”
mentioning
confidence: 99%